Histopathology and Liver Activities of Local Rabbit (Lepus sp) which Given Calliandra calothyrsus Meissn. Leaf Meals and Pineapple (Ananas comosus L.) Peels - Wiranatha, I Gede; Setyawati, Iriani; Wiratmini, Ngurah Intan (Metamorfosa: Journal of Biological Sciences, 2019)
The aimed of this study was to determine the effect of feed containing various concentrations of Calliandra calothyrsus Meissn. leaf meal mixed with pineapple peels and concentrate feed on histopathology and the activity of liver of local rabbit (Lepus sp). This study used a Post-Test Only Control Group Design, using 24 local male rabbits divided into 4 groups of feed treatment namely P0 = concentrate feed as control; P1 = mixture of 15% of calliandra leaf meal (CLM), 30% of pineapple peels (PP) and 55% of commercial feed (CF); P2 = 30% of CLM, 30% of PP and 40% of CF; and P3 = 45% of CLM, 30% of PP and 25% of CF). The treatments were given for 60 days and used 6 replicates for each group. The data were analyzed statistically by SPSS program version 22. The research results showed the increase of calliandra leaf meal levels in concentrated feed which were added 30% of pineapple peels still caused liver damage namely fatty degeneration, necrosis and congestion. It increased the ALT level, but did not affect the AST level in local rabbit serum.